The impact of financial participation on workers' compensation - Martyn Andrews; Lutz Bellmann; Thorsten Schank; Richard Upward (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
We investigate the impact of financial participation (profit-sharing and share ownership) on workers' total compensation. Some workers' representatives have argued against the introduction of profit-sharing because they fear that profit-sharing would be a way for firms to reduce the marginal cost of hiring workers, while at the same time transferring some of the risk of variable profits from firms to workers. We find that workers in plants which operate financial participation schemes earn significantly more: 25% in the case of profit-sharing and 18% in the case of share ownership. However, econometric models which deal with selection by plants and workers into profit-sharing schemes suggest that the effect on total compensation is much smaller: between 4% (from a difference-in-differences regression) and 2.5% (from a comparison of matched pairs). We find no evidence that high-skilled white-collar workers benefit more strongly from profit-sharing schemes.
Keywords: J33; C23; 330; Lohnhöhe; IAB-Betriebspanel; Gewinnbeteiligung; Kapitalbeteiligung; Qualifikationsniveau